2003
DOI: 10.1002/chir.10306
|View full text |Cite
|
Sign up to set email alerts
|

Secondary phosphine oxides: tautomerism and chiral recognition monitored by multinuclear NMR spectroscopy of their Rh2[(R)‐MTPA]4 adducts

Abstract: Six secondary phosphine oxides and their tautomeric equilibria as free ligands and in the presence of an equimolar amount of the chiral dirhodium complex Rh* are described and discussed. Discrimination of enantiomers is easily possible by inspecting the (31)P NMR resonances; some (1)H and (13)C NMR resonances are useful as well. H/D exchange of the acidic protons in the phosphine oxides takes place with acetone-d(6), the solvent additive, after some hours but does not obscure the chiral recognition experiment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…The gold loadings of precatalysts 2a and 2a.PEG were determined to be 0.037 mmol g -1 and 0.16 mmol g -1 , respectively, using ICP-OES. The solid state 31 P NMR spectra of 2a and 2a.PEG confirm the presence of a Au----P interaction which is clearly evident from the low field chemical shifts of  27.1 and 24.5 ppm, respectively; for comparison the 31 P NMR signals for polymers 1a and 1a.PEG appear at  -5 and -10.4 ppm, respectively (see ESI file for full details); these complexation shifts 39 are similar to previously reported values. 40 The 13 C CP/MAS NMR spectra of 1a and 1a.PEG and 2a and 2a.PEG contain a set of characteristic signals between  124-144 ppm associated with the imidazolium ring and the aromatic carbon atoms as well as signals in the range  11-50 ppm which correspond to the methyl groups attached to the imidazolium ring and the aliphatic carbon atoms of the polystyrene backbone (see ESI file for full details).…”
Section: Synthesis and Characterization Of Phosphine-modified Gold Prsupporting
confidence: 89%
“…The gold loadings of precatalysts 2a and 2a.PEG were determined to be 0.037 mmol g -1 and 0.16 mmol g -1 , respectively, using ICP-OES. The solid state 31 P NMR spectra of 2a and 2a.PEG confirm the presence of a Au----P interaction which is clearly evident from the low field chemical shifts of  27.1 and 24.5 ppm, respectively; for comparison the 31 P NMR signals for polymers 1a and 1a.PEG appear at  -5 and -10.4 ppm, respectively (see ESI file for full details); these complexation shifts 39 are similar to previously reported values. 40 The 13 C CP/MAS NMR spectra of 1a and 1a.PEG and 2a and 2a.PEG contain a set of characteristic signals between  124-144 ppm associated with the imidazolium ring and the aromatic carbon atoms as well as signals in the range  11-50 ppm which correspond to the methyl groups attached to the imidazolium ring and the aliphatic carbon atoms of the polystyrene backbone (see ESI file for full details).…”
Section: Synthesis and Characterization Of Phosphine-modified Gold Prsupporting
confidence: 89%
“…It was shown that the tautomer A is generally favored in the free ligand whereas the equilibrium is strongly shifted toward the tautomer B in the presence of Rh * (1 : 1 molar ratio) including 103 Rh, 31 P coupling information in the 31 P NMR signal. This is a proof for the much larger binding energy in the latter case 23…”
Section: Phosphanes: Category (I) Ligandsmentioning
confidence: 63%
“…This was proved by deuterium exchange experiments and IR spectroscopic measurements in the 1960s. 15 In 2004, Pietrusiewicz, Duddeck and co-workers suggested 16 from NMR studies that the fast kinetics of the tautomeric equilibrium is due to the migration of an acidic proton. In this line, Hong and co-workers 17 proposed two reaction pathways for the transformation of SPOs to the corresponding PA (Scheme 2), based on DFT calculations.…”
Section: Stereoelectronic Properties Of Sposmentioning
confidence: 99%